Phase comparison and equation of state for Ta2O5 - Brennan, Matthew C; Rehn, Daniel A; Huston, Larissa Q; Sturtevant, Blake T (Journal of physics. Condensed matter, 2024)
Tantalum pentoxide (Ta2O5) is among the most technologically useful heavy transition metal oxides. Unfortunately, its crystal structure is the subject of long-standing and unresolved disagreement. Among other consequences, this uncertainty has made it impossible to formulate a robust high pressure equation of state for Ta2O5. Here, we report the results of high pressure x-ray diffraction experiments indexed against a comprehensive list of proposed Ta2O5phases. Five of the proposed phases produce good matches to experimental observations, and the compressibility parameters for these phases are all consistent within uncertainty. This means that regardless of the particular phase chosen, the Ta2O5equation of state can be described with bulk modulusK0=138±3.68 GPa and pressure derivativeK0'=1.82±0.45. Combining these experimental results with new density-functional theory calculations allows us to identify theλphase as the best structural model of Ta2O5at ambient conditions.Tantalum pentoxide (Ta2O5) is among the most technologically useful heavy transition metal oxides. Unfortunately, its crystal structure is the subject of long-standing and unresolved disagreement. Among other consequences, this uncertainty has made it impossible to formulate a robust high pressure equation of state for Ta2O5. Here, we report the results of high pressure x-ray diffraction experiments indexed against a comprehensive list of proposed Ta2O5phases. Five of the proposed phases produce good matches to experimental observations, and the compressibility parameters for these phases are all consistent within uncertainty. This means that regardless of the particular phase chosen, the Ta2O5equation of state can be described with bulk modulusK0=138±3.68 GPa and pressure derivativeK0'=1.82±0.45. Combining these experimental results with new density-functional theory calculations allows us to identify theλphase as the best structural model of Ta2O5at ambient conditions.